A short discourse on reflexives: a reply to Cunnings (2016). Issue 4 (17th October 2016) - DILLON, BRIAN
Abstract : In his article, Parsing and working memory in bilingual sentence processing, Cunnings invites us to consider the hypothesis that important differences in how L1 and L2 populations process sentences stem from differences in how these speakers store and retrieve linguistic encodings in memory during the course of sentence comprehension (Cunnings, 2016). Specifically, he proposes that L2 speakers are more susceptible to similarity-based retrieval interference than their L1 counterparts, and L2 speakers weight discourse cues more heavily than syntactic cues when resolving open linguistic dependencies via memory retrieval. I find these to be interesting hypotheses that merit further investigation, especially in light of the prominence that these issues currently enjoy in L1 processing research. Nonetheless, I sound a note of caution: these claims go quite a bit beyond what is currently known, either theoretically or empirically. This makes support for these claims weak at present, but happily, this state of affairs offers clear directions for future research.